The socio-materiality of parental style: Negotiating the multiple affordances of parenting and child welfare within the new child surveillance technology market. Issue 11 (14th November 2016) - Bettany, Shona M.; Kerrane, Ben
Abstract : Purpose: This study aims to offer understanding of the parent – child relationship by examining, through a socio-material lens, how one aspect of the new child surveillance technology market, child GPS trackers (CGT), are rejected or adopted by families, highlighting implications for child welfare, privacy and children's rights policy. Design/methodology/approach: The authors gathered netnographic data from a range of online sources (parenting forums, online product reviews, discussion boards) that captured parental views towards the use of CGT and stories of the technology in use and theorize the data through application of a novel combination of neutralisation and affordance theory. Findings: The research reveals how critics of CGT highlight the negative affordances of such product use (highlighting the negative agency of the technology). Parental adopters of CGT, in turn, attempt to rationalize their use of the technology as a mediator in the parent – child relation through utilisation of a range of neutralisation mechanisms which re-afford positive product agency. Implications for child welfare and policy are discussed in the light of those findings. Originality/value: The paper presents an empirical, qualitative understanding of parents negotiating the emergence of a controversial new child-related technology – CGT – and its impact upon debates in the field of parenting and childhood; develops the theory of parental style towards parental affordances, using a socio-material theoretical lens to augment existing sociological approaches; and contributes to the debates surrounding child welfare, ethics, privacy and human rights in the context of child surveillance GPS technologies.